Hp → Hp boundedness implies Hp → Lp boundedness - Yongsheng Han; Ji Li; Guozhen Lu; Peiyong Wang (Forum Mathematicum, 2011)
On 2 May 2019, a recovery operation involving a 137Cs source in a research irradiator resulted in the breach of a source capsule containing approximately 77.1 TBq. Following this incident, the dispersal characteristics of the radioactive material were evaluated in the context of emergency response. The results showed that the dispersal behavior with the building ventilation system was consistent with previous recommendations for response to a radiological dispersal device in guidance first proposed in 2006. The 2006 guidelines stated that for most modern large buildings, intervention via ventilation systems is not likely to be an effective countermeasure.